Percepção de saúde no Brasil: uma análise das diferenças por sexo dos trabalhadores - Castro, Bruna Naiara de (2017)
Health is relevant to economic agents, since it contributes directly to the people´s well-being, and constitutes part of human capital and, for these reason, health affects a productivity and individual´s incomes. Either individual decisions and public policies that affect health have been doing cruxcial effects on economic development, also constitute a channel for an revenue distribution policie and fight against poverty. This study analyzes the differences of health conditions of male and female workers in Brazil in 2008, using as measure the perception of health of the researched people by the supplement of PNAD (Pesquisa Nacional por Amostra de Domicílios) of 2008. In the applied methodology, firstly was made descriptive statistical analyzis, also were estimated probit models in two stages to capture the contributions of the socioeconomic caratteristiche to the person´s health conditions occupied by sex. The main results were that women presented worst health perceptions than men in almost all socioeconomic variables analyzed. Health policies need to address the specific needs of men and women, and it is also believed that reducing gender inequality can reduce differences in health perceptions of gender.